Implementasi Augmented Reality (AR) Laboratory Terhadap Pemahaman Konsep Siswa Pada Materi Listrik Dinamis - Silpia Pirgianti; Ali Ismail; Dini Andriani (Universitas Garut, 2026)
This study aims to determine the improvement and effectiveness of students' conceptual understanding of dynamic electricity through the implementation of an Augmented Reality (AR) Laboratory application. A quantitative approach with a quasi-experimental method was used, employing a non-equivalent control group design. The participants were two tenth-grade classes at SMK Negeri 2 Garut, consisting of an experimental class (n = 26) taught using the AR Laboratory application and a control class (n = 24) taught using a conventional problem-solving method. The research instrument consisted of 12 validated and reliable essay items measuring conceptual understanding indicators (interpreting, exemplifying, classifying, explaining, and inferring). The mean pretest score was 8.88 for the control class and approximately 16.2 for the experimental class, while the mean posttest score increased to 22.92 for the control class and 29.12 for the experimental class. Because the data were normally distributed but not homogeneous, hypothesis testing was carried out using an independent samples t-test with equal variances not assumed, which yielded a significance value (2-tailed) of less than 0.001, indicating a significant difference between the two groups. The N-Gain analysis showed a mean score of 0.5433 (moderate category) for the experimental class and 0.4577 (moderate category) for the control class. The Cohen's d effect size was 0.990, categorized as moderate, indicating that 83.9% of the experimental group scored above the control group's average. These findings indicate that the implementation of the AR Laboratory application has a significant effect and provides a greater improvement in students' conceptual understanding of dynamic electricity compared to conventional learning.